2016
DOI: 10.1016/j.rbo.2015.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do tratamento cirúrgico da síndrome do túnel do carpo com anestesia local

Abstract: Como citar este artigo: Barros MFFH, et al. Avaliação do tratamento cirúrgico da síndrome do túnel do carpo com anestesia local. Rev Bras Ortop. 2015. http://dx.RBO-964; No. of Pages 4 r e v b r a s o r t o p . 2 0 1 5;x x x(x x):xxx-xxx w w w . r b o . o r g . b r Artigo original Avaliação do tratamento cirúrgico da síndrome do túnel do carpo com anestesia local ଝ On-line em xxx Palavras-chave: Síndrome do túnel do carpo Anestesia local Epinefrina r e s u m o Objetivo: Avaliar os resultados e as complicaç ões… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…There were no cases of necrosis, hematoma, or any postoperative complications. 4 In a study by Barros et al, 10 the authors concluded that the WALANT technique in the surgical treatment of CTS is effective and safe. The study demonstrated a significant improvement in postoperative pain, and 75% of patients reported that the procedure is equivalent to or better than venipuncture, showing satisfaction with the technique and its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no cases of necrosis, hematoma, or any postoperative complications. 4 In a study by Barros et al, 10 the authors concluded that the WALANT technique in the surgical treatment of CTS is effective and safe. The study demonstrated a significant improvement in postoperative pain, and 75% of patients reported that the procedure is equivalent to or better than venipuncture, showing satisfaction with the technique and its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…No pós-operatório, não houve casos de necrose, hematoma ou qualquer complicação. 4 Em outro estudo, Barros et al 10 concluíram que a técnica WALANT é eficaz e segura no tratamento cirúrgico da STC. A pesquisa evidenciou uma melhora significativa da dor no pósoperatório, e 75% dos pacientes relataram que o procedimento se equivale ou é melhor do que uma punção venosa, evidenciando uma satisfação com a técnica e a sua eficácia.…”
Section: Discussionunclassified